1953
DOI: 10.1021/ac60084a010
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Flame Photometric Determination of Sodium in Portland Cement

Abstract: The sodium content of portland cement is routinely determined by flame photometry. Some flame photometers were found consistently to indicate sodium contents of less than zero for certain cements.In addition, different brands of flame photometers almost never gave identical results for any cement.A study of the method showed that flame photometers having wide effective band widths gave low, often negative results, because of the inhibiting effect of silica on the emission of calcium oxide in the region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1954
1954
1969
1969

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Silica, present in varying amounts in cement, inhibits the emission of calcium. Because the standard solutions used do not normally contain siHca, this leads to somewhat low results for sodium (by a few hundredths of a percent) unless the silica is removed [15]. In fact, one or two cements manufactured domestically contain such a low contentj of Na20 that some flame photometers indicate!…”
Section: Causes Of Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica, present in varying amounts in cement, inhibits the emission of calcium. Because the standard solutions used do not normally contain siHca, this leads to somewhat low results for sodium (by a few hundredths of a percent) unless the silica is removed [15]. In fact, one or two cements manufactured domestically contain such a low contentj of Na20 that some flame photometers indicate!…”
Section: Causes Of Variationsmentioning
confidence: 99%
“…Care should be taken that the thumb pressures are applied entirely to the surface of the mortar, and not to the surface of the mold. The specified thumb pressure of between 15 and 20 lb may be measured by molding the briquets on a platform scale or on other suitable apparatus that will indicate the pressure exerted. (7) Variations in techniques of finishing specimens.…”
Section: Causes Of Variationsmentioning
confidence: 99%
“…Silica, present in varying amounts in cement, inhibits the emission of calcium. Because the standard solutions used do not normally contain silica, this leads to somewhat low results for sodium (by a few hundredths of a percent) unless the silica is removed [18]. In fact, one or two cements manufactured domestically contain such a low content of Na 2 0 that some flame photometers indicate a slight negative Na 2 0 content if silica is not removed.…”
Section: Sodium Oxide and Potassium Oxidementioning
confidence: 99%
“…Diamond and Bean (5) have reported that at the wave length used for the photometric determinations of sodium, some interference is caused by calcium present in the solutions. However, all test solutions-standards (including zero), samples, and blanks-contained equal amounts of calcium carbonate (containing a slight amount of sodium oxide), thus compensating for the effect of calcium in the solutions.…”
Section: Experimental Workmentioning
confidence: 99%